THE ANALYSIS OF PREMIUM STRATEGY AND VEHICLE CLAIMS IN INCREASING REVENUES OF PT ASURANSI SINAR MAS TANGERANG - Anggraini, Anggun (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2018)
This research conducted  to determine the premium strategy and insurance claims at PT. Asuransi Sinar Mas Branch of Tangerang period 2005-2015 using SWOT analysis method. Through SWOT analysis can be known the premium strategy that can be applied by the company, This research used the qualitative and quantitative study Methods (combined method). Overall research results show that the SWOT analysis to increase the premium can be seen through the target premium set during one year that has reached the target by way of marketing mix, cooperate with some leasing, the company issued a car insurance product no claim money back, and with the tariff change from OJK where its motor vehicle line rises so that the premium goes bigger, as well as the number of new vehicle types out so that it becomes the stimulus for the customers to change the vehicle and usually insured. While the claim strategy used to suppress the number of claims that is with the acceptance control that is from the year 2005-2010 amounted to 9.51% decreased to 8.35% starting in 2011-2015 in the hope of increasing the underwriting income